2018
DOI: 10.1136/heartjnl-2017-312150
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of new-onset atrial fibrillation following coronary artery bypass graft surgery

Abstract: Each year, ~800 000 people undergo CABG worldwide; >264 000 will develop post-CABG AF. Onset is typically 2-3 days post-CABG and episodes last, on average, several hours. Effective prophylaxis and management is urgently needed to reduce associated risks of adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 28 publications
7
77
2
5
Order By: Relevance
“…Supporting our results, Filardo et al had the same result from their study [3] , and they reported that both ICU time and mechanical ventilation time were statistically associated with postoperative AF in the univariate analysis, but mechanical ventilation time is the only one correlated signi cantly with AF after analyzed by logistic analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Supporting our results, Filardo et al had the same result from their study [3] , and they reported that both ICU time and mechanical ventilation time were statistically associated with postoperative AF in the univariate analysis, but mechanical ventilation time is the only one correlated signi cantly with AF after analyzed by logistic analysis.…”
Section: Discussionsupporting
confidence: 90%
“…within the incidence of prior studies [1][2] [3] . Age is one of the most consistent risk factors for postoperative AF in many previous literature [4] [15] , which was also supported by our research.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, despite having medications for POAF prophylaxis and early treatment, the incidence of postoperative atrial fibrillation has remained relatively constant after isolated CABG. 4 Increased postoperative glucose variability (GV) may contribute to atrial fibrillation and major adverse events after CABG and may be a feasible therapeutic target to reduce these poor outcomes. [5][6][7] GV refers to swings in glucose levels throughout the day, including hypoglycemic episodes, hyperglycemic episodes, and postprandial changes.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative atrial fibrillation (POAF) affects 15% to 30% of patients undergoing cardiac surgery [1,2]. It not only increases the length of hospitalization but has also been associated with higher postoperative morbidity and mortality [2].…”
Section: Invited Commentarymentioning
confidence: 99%